2022
DOI: 10.3389/fnagi.2021.802582
|View full text |Cite
|
Sign up to set email alerts
|

GABAA Receptors in Astrocytes Are Targets for Commonly Used Intravenous and Inhalational General Anesthetic Drugs

Abstract: Background: Perioperative neurocognitive disorders (PNDs) occur commonly in older patients after anesthesia and surgery. Treating astrocytes with general anesthetic drugs stimulates the release of soluble factors that increase the cell-surface expression and function of GABAA receptors in neurons. Such crosstalk may contribute to PNDs; however, the receptor targets in astrocytes for anesthetic drugs have not been identified. GABAA receptors, which are the major targets of general anesthetic drugs in neurons, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…In addition to mitochondria, astrocytes present a wide range of likely general anesthetic targets that probably modulate emergence dynamics (see review 75 ) including even GABA A receptors. 143 Microglia, the immune cells of central nervous system, also appear to modulate emergence from sedation and analgesia thresholds. 144 The different pharmacodynamics of these diverse targets distributed among different cells surrounding a synapse may explain why reversal agents can accelerate certain behaviors but not others, and the time required for general anesthetics to dissociate from these multiple sites may contribute to delayed recovery.…”
Section: Presynaptic and Glial Mechanisms May Need To Be Considered T...mentioning
confidence: 99%
“…In addition to mitochondria, astrocytes present a wide range of likely general anesthetic targets that probably modulate emergence dynamics (see review 75 ) including even GABA A receptors. 143 Microglia, the immune cells of central nervous system, also appear to modulate emergence from sedation and analgesia thresholds. 144 The different pharmacodynamics of these diverse targets distributed among different cells surrounding a synapse may explain why reversal agents can accelerate certain behaviors but not others, and the time required for general anesthetics to dissociate from these multiple sites may contribute to delayed recovery.…”
Section: Presynaptic and Glial Mechanisms May Need To Be Considered T...mentioning
confidence: 99%
“…14 Equally intriguing was our recent finding that glia, and in particular, astrocytes-the most abundant cells in the brain-express anesthetic-sensitive extrasynaptic GABA A receptors. 77 Activation of astrocytic GABA A receptors by sevoflurane and etomidate triggers an astrocyte-toneuron crosstalk that increases the tonic current in neurons. Interestingly, both the anesthetic drugs and proinflammatory factors (e.g., IL-1β) engage the same cytosolic pathways to enhance cell surface expression of α5GABA A Rs.…”
Section: Properties Of Extrasynaptic Gaba a Receptors Your Data Caref...mentioning
confidence: 99%
“…A deeper knowledge of the formation of consciousness and the operation of different brain regions may result from research on the interplay between the two domains. Additionally, there is mounting proof that glial cells are involved and that sevoflurane acts on their GABA A receptors (Woll et al, 2018;Chung et al, 2022), thereby influencing their function. (2022) ↑indicated that the time is increasing, the EEG power increased or the c-Fos positive cells was increased.…”
Section: Future Directionmentioning
confidence: 99%